2018
DOI: 10.1155/2018/1242901
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Ketonemia and Development of the Fetal Central Nervous System

Abstract: Glucose is the major source of energy for the human brain which in turn uses ketone bodies as a supplement for energy deficit in glucose cell deficiency conditions. Pregnancy complicated by gestational diabetes is a condition associated with significantly increased risk of ketonemia development. The data available proves a changing influence of ketones on the central nervous system during fetal life and in adults as well. Ketone bodies freely pass through the placenta. They can affect fetal growth and organ da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…It is known that in the latter half of normal pregnancy, maternal metabolism is converted to a catabolic state, during which the increased lipolysis provides fatty acids to be utilized in ketogenesis (24). The ketone bodies produced are used as a maternal energy source in place of glucose, which is mostly utilized by the fetus (25). Previous studies have also detected elevated levels in ketone bodies in pregnant women with high fasting glucose concentrations (26) and in association with GDM (3,4,27).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that in the latter half of normal pregnancy, maternal metabolism is converted to a catabolic state, during which the increased lipolysis provides fatty acids to be utilized in ketogenesis (24). The ketone bodies produced are used as a maternal energy source in place of glucose, which is mostly utilized by the fetus (25). Previous studies have also detected elevated levels in ketone bodies in pregnant women with high fasting glucose concentrations (26) and in association with GDM (3,4,27).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the presence of increased FHR pattern III is not only due to maternal dehydration from exposure to ketone bodies but also due to neurologic alterations in some fetuses exposed to maternal ketones. Support for our hypothesis is provided by the documented impact ketonemia has on CNS excitability in adult offspring as well as on the fetus [9]. In addition, several theories have attempted to explain the mechanisms underlying the impact of ketones on CNS functioning.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, ketones diffuse freely across the placenta and can be used as a source of energy by the fetus [7], so Kurepa et al suggested that a mother's hyperketonemia plays a role in fetal development during pregnancy [8]. Previous studies have also shown that maternal ketones elicit potentially detrimental changes in the neurologic statuses of animals and human beings [9]. For example, a ketonic state in diabetic pregnant women has been associated with decreased intelligence and impaired fine motor skills in offspring [10].…”
Section: Introductionmentioning
confidence: 99%
“…For the developing central nervous system (CNS), ketones not only can act as an energy source but also be used in lipogenesis as a lipid precursor. Moreover, ketones can modulate CNS functions, notably by partaking in adenosine triphosphate (ATP) synthesis and carbon pathway ( Edmond et al, 1985 ; Williamson, 1985 ; Bronisz et al, 2018 ). While ketones possess important roles for fetal and neonate development, the consumption of a ketogenic diet and its implication during pregnancy is complex and it remains largely unclear whether it is beneficial or detrimental.…”
Section: Specific Nutrient Imbalance and Inflammationmentioning
confidence: 99%